Validity and reliability of the Turkish orebro musculoskeletal pain screening questionnaire-short form - ATA TAY, HİLAL; CAN, HİLAL BAŞAK (My University, 2022)
BACKGROUND: The Orebro Musculoskeletal Pain Screening Questionnaire (OMPSQ) is one of the most recognized and widely used instruments for identifying the risk of pain chronicity.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Public Health, Environmental and Occupational Health; Epidemiology; Health Sciences; Social Sciences & Humanities; Pain; musculoskeletal disorders; psychosocial factors; yellow flags; chronicity; FEAR-AVOIDANCE BELIEFS; PREDICTIVE-VALIDITY; VERSION; VALIDATION; CONSTRUCT; RISK